2003
DOI: 10.1207/s15327663jcp1304_08
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Spokesperson Trustworthiness on Message Elaboration, Attitude Strength, and Advertising Effectiveness

Abstract: Recent research has shown that information presented by untrustworthy endorsers is likely to be thoughtfully elaborated, whereas information presented by trustworthy endorsers is likely to be unthinkingly accepted (Priester & Petty, 1995). Study 1 manipulated argument quality and assessed cognitive responses to demonstrate that this influence of trustworthiness on persuasion holds for familiar endorsers likely to be used in actual advertisements. Study 2 demonstrated that trustworthiness can be influenced by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 275 publications
(176 citation statements)
references
References 25 publications
5
149
1
4
Order By: Relevance
“…That is, fast disclaimers appear to undermine purchase intention directly rather than by prompting consumers to scrutinize disclaimer content more carefully. Past research has shown that messages from untrustworthy sources elicit more attention and scrutiny than messages from trustworthy sources do (Priester and Petty 1995). Because increased attention to positive content should not reduce trust (and should, if anything, increase it), the fact that fast positive disclaimers reduced trust in our research suggests that our findings are unlikely to have resulted from increased elaboration from suspicious consumers.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…That is, fast disclaimers appear to undermine purchase intention directly rather than by prompting consumers to scrutinize disclaimer content more carefully. Past research has shown that messages from untrustworthy sources elicit more attention and scrutiny than messages from trustworthy sources do (Priester and Petty 1995). Because increased attention to positive content should not reduce trust (and should, if anything, increase it), the fact that fast positive disclaimers reduced trust in our research suggests that our findings are unlikely to have resulted from increased elaboration from suspicious consumers.…”
Section: Discussionmentioning
confidence: 43%
“…We have proposed that fast disclaimer speed acts as a negative heuristic cue, leading consumers to view the advertised product-without conscious elaboration of the content of the message-as suspicious and perhaps unworthy of purchase. However, a plausible alternative explanation for our results is that fast communications cause consumers to be suspicious of the communicator's intent and, consequently, to attend more carefully to the content of the communication (Petty and Cacioppo 1986;Priester andPetty 1995, 2003). Such scrutiny could be stronger with trust-unknown or nottrusted brands than with trusted brands.…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…The question of 'what attributes are desirable for an endorser to possess?' (Priester and Petty, 2003) is quite relevant in a situation of tough competitions for consumer hearts.…”
Section: Theoretical Substantiationmentioning
confidence: 99%